NEW TECHNOLOGIES AND THEIR IMPACT ON FOREIGN LANGUAGE TEACHER PROFESSIONAL BURNOUT - Liliya Morska; Krzysztof Polok; Małgorzata Bukowska; Iryna Ladanivska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2022)
Because of the dynamic and rapid development of digital technologies, teachers are facing more than ever challenging issues related to coping with educational innovations. This situation has become ultimately evident under COVID-19 quarantine and the necessity to work remotely. Such requirements induce extra pressure on teachers, which causes excessive stress, often leading to emotional and professional burnout. In our paper, we aim to focus on the types of impact (positive or negative) of digital technologies in relation to foreign language teachers' age and experience and the level of professional burnout. Specific emphasis is put on the study of coronavirus-related remote learning mode circumstances. To reach the research goal, a mixed method was used, engaging 140 English language teachers from 18 Polish schools, Silesia region, with a questionnaire and a semi-structured interview as the tools used in the quantitative and qualitative stages of the study. The research findings show that even though teachers are ready to integrate technologies in the classroom, they are vulnerable to technical problems which often occur during the lessons, causing the feeling of disappointment, frustration, anxiety, and lowering the efficiency of teachers' professional performance. The implications of the study suggest that the professional support for teachers in technology use, better working conditions, and equipping language classrooms with good quality digital devices should serve as the best remedy against teacher burnout.